2022
DOI: 10.1186/s13071-022-05180-3
|View full text |Cite
|
Sign up to set email alerts
|

Preventive efficacy of six monthly oral doses of Simparica Trio®, Heartgard® Plus, and Interceptor® Plus against a macrocyclic lactone-resistant strain (ZoeLA) of heartworm (Dirofilaria immitis) in dogs

Abstract: Background Administration of four to six consecutive monthly doses of 24 µg/kg moxidectin alone shows high effectiveness in preventing the maturation of macrocyclic lactone (ML)-resistant heartworm strains, Dirofilaria immitis JYD-34 and ZoeLA. This laboratory study evaluated the efficacy of six consecutive monthly oral doses of Simparica Trio® (moxidectin/sarolaner/pyrantel) compared to six monthly doses of either Heartgard® Plus (ivermectin/pyrantel) or Interceptor® Plus (milbemycin oxime/pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Over all studies, preventive efficacy of moxidectin against resistant strains was between 95.9 and 99.3%, while the efficacy of ivermectin and milbemycin was between 8.5 and 63.9%. Dogs receiving oral moxidectin had significantly lower geometric mean worm counts than dogs receiving Heartgard ® Plus, Interceptor ® Plus or no heartworm prevention (80,81). It should be noted that the oral moxidectin dose in all studies was ≥24 μg/kg, which was considered the optimal dose in a dose-finding study on resistant D. immitis strains (82).…”
Section: Laboratory Efficacy Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Over all studies, preventive efficacy of moxidectin against resistant strains was between 95.9 and 99.3%, while the efficacy of ivermectin and milbemycin was between 8.5 and 63.9%. Dogs receiving oral moxidectin had significantly lower geometric mean worm counts than dogs receiving Heartgard ® Plus, Interceptor ® Plus or no heartworm prevention (80,81). It should be noted that the oral moxidectin dose in all studies was ≥24 μg/kg, which was considered the optimal dose in a dose-finding study on resistant D. immitis strains (82).…”
Section: Laboratory Efficacy Studiesmentioning
confidence: 99%
“…Five of the seven studies also reported the number of dogs testing positive for heartworm antigen and microfilariae at different time points (79)(80)(81). At the final evaluation time point, one dog receiving the extended-release moxidectin injectable PH12 tested positive for heartworm antigen in one of two studies, whereas all (6 of 6) or most (5 of 6) dogs receiving ivermectin, milbemycin oxime, or no heartworm preventive tested positive for heartworm antigen and microfilariae at the final evaluation time points in the two studies.…”
Section: Laboratory Efficacy Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent laboratory study, Simparica Trio, containing 24 µg/kg moxidectin, 1.2 mg/kg sarolaner and 5 mg/ kg pyrantel, and Heartgard Plus and Interceptor Plus (n = 6) were administered in six consecutive monthly oral doses at the labeled dose rates after receiving an inoculation of 50 ZoeLA strain D. immitis L3 on day −30 [50]. Dogs were necropsied approximately 9 months post-inoculation and evaluated for the presence of circulating MF and heartworm antigen on days 180, 210, and 236.…”
Section: Oral Moxidectinmentioning
confidence: 99%
“…No dogs treated with Simparica Trio tested positive for the presence of circulating MF at any time during this study, with only two of the six dogs testing positive for heartworm antigen. All six dogs treated with Heartgard Plus and Interceptor Plus had adult worms present at necropsy, with a geometric mean of 32.5 and 22.8 adults recovered, and preventive efficacy of 8.5% and 35.9%, respectively (Table 3) [50]. On day 236, all Heartgard Plus-and Interceptor Plustreated dogs were positive for the presence of heartworm antigen, and five of the total six dogs for each group were positive for circulating MF, indicating the possibility of infected dogs being able to transmit ML-resistant heartworm strains despite proper use of these preventive products.…”
Section: Oral Moxidectinmentioning
confidence: 99%